1983
DOI: 10.1143/jjap.22.l343
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Excluded Volume Effect and Alignment of Nematic Liquid Crystal in a Sandwich Cell

Abstract: It is shown that the orientation dependent excluded volume interaction between elongated nematic molecules and the cell walls always favors the planar alignment of nematic liquid crystals. For thermotropic liquid crystals the anchoring energy of this effect amounts to several erg/cm2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…Our results show that, for a rubbed polymer surface, a biaxial asymmetry exists on a molecular level. It is then reasonable to attribute the orientation of the LC, which is placed in contact with the oriented polymer surface, to an anisotropic interactions between the two systems, the dominant ones being the excluded volume interaction [28,30] arising from steric effects between the LC rods and the surface, and the intermolecular interaction [28,[31][32][33][34].…”
Section: Theory Of Lc Alignment: Maximum Overlap Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that, for a rubbed polymer surface, a biaxial asymmetry exists on a molecular level. It is then reasonable to attribute the orientation of the LC, which is placed in contact with the oriented polymer surface, to an anisotropic interactions between the two systems, the dominant ones being the excluded volume interaction [28,30] arising from steric effects between the LC rods and the surface, and the intermolecular interaction [28,[31][32][33][34].…”
Section: Theory Of Lc Alignment: Maximum Overlap Modelmentioning
confidence: 99%
“…It has been shown that for a nematic LC consisting of rod-like units which is positioned on a clean, well-defined flat surface, the anisotropic part of the excluded volume interaction has the general form [30] DW ex Asin 2 a 30…”
Section: Theory Of Lc Alignment: Maximum Overlap Modelmentioning
confidence: 99%
“…[21] When the free surface is covered with a segregated layer, the excluded volume effect from the plane solid substrate should dominate. [22] An alternative explanation can be the tendency to adopt a planar orientation of the mesogenic groups in the segregated PBMA-b-PAz. [14b] It is noteworthy that the LC mesogens and MPS domain orientations in pure LC polymer films were unaffected by the surface energy of the substrate surface.…”
mentioning
confidence: 99%
“…In order to confirm the groove theory, a nanosized ultrafine pattern with a simple periodical shape is necessary for analysis and has not been investigated to date. [4][5][6][7][8][9][10] Therefore a nanosized pattern is interesting from the theoretical and practical points of view. However, LC alignment using nanosized and well-regulated patterns is not well understood.…”
Section: Introductionmentioning
confidence: 99%